Arctic ecosystems in peril : report of the Arctic Goose Habitat Working Group - Batt, Bruce D. J.; U.S. Fish and Wildlife Service.; Arctic Goose Habitat Working Group. ([Washington, D.C. : U.S. Fish and Wildlife Service, 1997)
Not distributed to depository libraries in a physical form. "A special publication of the Arctic Goose Joint Venture of the North American Waterfowl Management Plan." Includes bibliographical references. Mode of access: Internet.